Construction of the ecological security pattern of Mu Us sandy land on the basis of the “Source − Resistance − Corridor” theory - Jiamin Li; Li’e Liang; Yan Chao; Xiaohan Wang; Mingming Qiu; Pingping Luo; Yonghua Zhu (Ecological Indicators)
With the development of the social economy, the destruction of the ecological environment is becoming increasingly severe, threatening the sustainable development of the region. The construction of an ecological security pattern (ESP) helps ensure regional ecological security and sustainable development while providing ideas for addressing these challenges. Taking the ecologically vulnerable Mu Us sandy land (MUS) as a case study, this paper constructs a ESP for the years 1980, 1990, 1995, 2000, 2005, 2010, 2015, and 2020 on the basis of the fundamental theory of “source-resistance-corridor” and with the “point-line-surface” integrated analysis method, and this paper delineates areas with different protection priorities. A total of 29 ecological source areas were identified across the eight periods, with uneven spatial distributions, and they were mainly concentrated in the southern grassland area and the northern marginal area, with an average proportion of 26.32%. Forty ecological corridors (ECs) were determined, revealing an overall annular distribution. Considering the ecological background conditions and current development status of the study area, it was divided into ecological protection areas, ecological restoration areas, and ecological construction areas, and targeted management zoning and optimization suggestions were proposed. Our findings are not only significant for optimizing the spatial layout of the MUS and maintaining regional ecological security but also provide a model and ideas for the construction of ESPs and environmental protection systems in similar desertification areas.